Identification of language in a cross linguistic environment - Merin Thomas; Dr Latha c A; Antony Puthussery (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
World has become very small due to software internationationalism. Applications of machine translations are increasing day by day. Using multiple languages in the social media text is an developing trend. .Availability of   fonts in the native language enhanced the usage of native text in internet communications. Usage of   transliterations of language   has become quite common. In Indian scenario current generations are   familiar to talk in native language but not to read and write in the native language, hence they started using English representation of native language in textual messages. This paper describes the   identification of the transliterated text in cross lingual environment .In this paper a Neural network model   identifies the prominent language in the text and hence the same can be used to identify the meaning of the text in the concerned language. The model is based upon Recurrent Neural Networks that found to be the most efficient in machine translations. Language identification can serve as a base for many applications in multi linguistic environment. Currently the South Indian Languages Malayalam, Tamil are identified from given text. An algorithmic approach of Stop words based model is depicted in this paper. Model can be also enhanced to address all the Indian Languages that are in use.